Contribution to the knowledge of Quadraseta pazca (Brennan and Jones, 1964) (Trombidiformes: Trombiculidae), including new host-association and locality records - Huang-Bastos, Matheus; Bassini-Silva, Ricardo [UNESP]; Arbex, Rafaela Luiza; Welbourn, Cal; Ochoa, Ron; Jacinavicius, Fernando de Castro; Barros-Battesti, Darci Moraes [UNESP] (Taylor & Francis, 2022)
The Neotropical genus Quadraseta Brennan has 15 valid species associated with small mammals and birds. Quadraseta pazca (Brennan and Jones, 1964) is the type species chosen by Brennan (1970) to describe the genus Quadraseta. This species was originally described parasitizing murids in Argentina and later recorded parasitizing cricetids in two different Brazilian states, Minas Gerais and São Paulo. In this study, we provide a redescription of Q. pazca based on the type series. The following characters separate this species from the others within the genus: palptibia lateral setae branched; adoral setae branched; one pair of clavate trichobothria (si); leg I genu with three solenidia (σ); and the base of microseta (ε) of leg I tarsus is proximal to the base of solenidion (ω). In addition, we also provide new locality and host-association records for this species in Brazil.
Keywords: Acarology; Chigger mite; ectoparasite; new records; South America